RISK MANAGEMENT IN THE CLINICAL LABORATOIRES - USE OF THE FAILURE MODES AND EFFECTS ANALYSIS (FMEA) - Tosheska-Trajkovska, Katerina; Kostovska, Irena; Labudovic, Danica; Brezovska, Julijana; Cekovska, Svetlana; Bogdanska, Jasna; Krstevska, Marija; Spasova, Natasa Toseska; Nikolov, Goran; Biljali, Sefedin; Topuzovska, Sonja (Journal of Morphological Sciences, 2019)
Introduction: Risk Management Process consists of a series of steps that, when undertaken  in  sequence, enable continual improvement in decision making. Failure Modes and Effects  Analysis (FMEA) is systematic method of identifying and preventing product and process problems before they occur. Objective: To present FMEA as a tool for risk managing and improvement in a public clinical laboratory. Methods: We studied the failure modes that might occur in the total testing process (TTP) . Each failure mode was ranked on estimated frequency of occurrence (O), detection (D) and severity (S), each on a scale of 1â€“4. Failure risks were calculated by Risk Priority Numbers (RPNs) = O Ã— D Ã— S. Results: We used FMEA, including technical risks as well as risks related to human failure in assessment of analytical procedures. FMEA was applied in two stages: at the beginning of the project and after the implementation of the proposed measures. The analytical method was broken down into process steps and we identified possible failure modes for each step. Failure modes with the highest RPN scores were subjected to corrective actions. Conclusion: We recommend risk analysis as an addition to the usual analytical validation, as the FMEA proved to be a reliable tool for detection of previously unidentified risks. Key words: FMEA, risk management, clinical laboratory